Strategy and planning for beef cow development based on land carrying capacity in South Tapanuli District - Hasibuan, Arif Sopiandin; Tafsin, Ma'ruf; Budi, Usman (Institute of Computer Science (IOCS), 2024)
South Tapanuli District has quite potential in developing beef cattle by maximizing the potential of land with various types of plantation and agricultural plants as a source of animal feed. The objectives to be achieved in this research are to analyze the availability of feed based on plantation crops and food crops that support beef cattle feed sources, analyze variables in beef cattle development in influencing the number of beef cattle populations, and analyze strategic factors that influence the success of developing beef cattle and formulating strategies to increase beef cattle production in South Tapanuli District. Multiple linear regression analysis was used to examine the data. The study's findings demonstrate the abundance of potential carrying capacity of the region's land, with plantation area having the capacity to support 1,420 beef cattle annually and agricultural land having the capacity to support 14,508 cattle annually.